2014
DOI: 10.1063/1.4893738
|View full text |Cite
|
Sign up to set email alerts
|

The effects of layering in ferroelectric Si-doped HfO2 thin films

Abstract: Atomic layer deposited Si-doped HfO2 thin films approximately 10 nm thick are deposited with various Si-dopant concentrations and distributions. The ferroelectric behavior of the HfO2 thin films are shown to be dependent on both the Si mol. % and the distribution of Si-dopants. Metal-ferroelectric-insulator-semiconductor capacitors are shown to exhibit a tunable remanent polarization through the adjustment of the Si-dopant distribution at a constant Si concentration. Inhomogeneous layering of Si-dopants within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The presence of ferroelectric shape of the P-V loop and XRD spectra for PS with HfO 2 filled into its microcavities, could still imply the presence of ferroelectricity in this work. The incorporation and encapsulation of Si could promote the ferroelectric phase transformation27. Though the mixture of HfO 2 with Si in the nanometer microcavities shown in this work is not entirely the same with the directly Si insertion into HfO 2 , The similar influence between them for the adjustment of ferroelectricity of HfO 2 could be expected.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The presence of ferroelectric shape of the P-V loop and XRD spectra for PS with HfO 2 filled into its microcavities, could still imply the presence of ferroelectricity in this work. The incorporation and encapsulation of Si could promote the ferroelectric phase transformation27. Though the mixture of HfO 2 with Si in the nanometer microcavities shown in this work is not entirely the same with the directly Si insertion into HfO 2 , The similar influence between them for the adjustment of ferroelectricity of HfO 2 could be expected.…”
Section: Resultsmentioning
confidence: 59%
“…It is due to the formation of Hf silicides embedded in Hf silicates from the decomposition of HfSi x O y , which has been well documented by many groups26. With Si adjustment, it is reasonable that HfO 2 exhibits a ferroelectric polarization27. Additionally, Johannes Müller28 and coworkers have reported the ferroelectricity in undoped hafnium oxide very recently.…”
Section: Resultsmentioning
confidence: 87%
“…The change of the ALD sequence of SiO 2 and HfO 2, as well as the ALD cycle ratio of SiO 2 and HfO 2, strongly affects the FE properties of Si‐doped HfO 2 films. Lomenzo et al reported that the P r of Si‐doped HfO 2 films with doping concentration of ≈5.5–5.7% decreased with increasing inhomogeneity of Si dopants, meaning that the portion of the non‐ferroelectric phases increased . Zhou et al found that the leakage current density of 10 nm‐thick Si‐doped HfO 2 film was smaller than 4 × 10 −5 A cm −2 even under a very large electric field of 3 MV cm −1 .…”
Section: Effects Of Dopantsmentioning
confidence: 99%
“…Second, the HfO 2 is probably not pure but with Si incorporation in this work, because the sputtering bombardment could carry Si into the HfO 2 in microcavities due to the fragility and the irregular shape of Si sidewall of porous microcavity; therefore, HfO 2 exhibits a ferroelectric polarization with Si adjustment. 26 It has been reported that the Si-doped HfO 2 exhibits a tunable remanent polariztion through the adjustment of the Si dopant distribution. 26 Meanwhile, considering the penetrating through among microcavities, the mixture of Si and HfO 2 leading to the non-pure HfO 2 state.…”
mentioning
confidence: 99%
“…26 It has been reported that the Si-doped HfO 2 exhibits a tunable remanent polariztion through the adjustment of the Si dopant distribution. 26 Meanwhile, considering the penetrating through among microcavities, the mixture of Si and HfO 2 leading to the non-pure HfO 2 state.…”
mentioning
confidence: 99%